PANCASILA AS THE IDEAL OF LAW IN INDONESIAN NATIONAL LEGAL AND RULE OF LAW SYSTEMS - Suroto Suroto (VIVA THEMIS, 2018)
ABSTRACTPancasila serves as an ideology foundation, a way of life, and the one that unites the nation in achieving the ideals of the nation. The position of Pancasila is very important for the life of society, nation, and state so that the status is firmly and clearly stated in the fourth paragraph of the preamble of the 1945 Constitution.The ideal of law of Pancasila in the Indonesian National Legal System (SHNI) is constitutive and regulative in its function to the Indonesian National Legal Rule System (SAHNI) with the norm of State Fundamental. Pancasila establishes the legal norms under it in stages. Lower legal norms are formed based on and derived from higher legal norm. Consequently, there is no conflict between higher and lower legal norms, and vice versa. Pancasila is the source of all sources of law, and should not be broader than the other sources of law. When the Indonesian people interpret it broader than that in their society, nation and state, it is not true.